High-Gain Circularly Polarized Rectangular Dielectric Resonator Antenna Array at 28 GHz for Millimeter-Wave Applications - Tarek S. Abdou; Alsayah A. M. Emhemed (African Journal of Advanced Pure and Applied Sciences, 2025)
This study presents a rectangular dielectric resonator antenna (RDRA) array designed to operate in the 28 GHz millimeter-wave (mmWave) spectrum. It achieves circular polarization (CP) by utilizing an innovative feed network with cross-slots. The DRA’s dimensions, relative to the free-space wavelength (λ₀), are 0.478λ₀ × 0.478λ₀ × 0.28λ₀. The 1 × 4 array demonstrates excellent performance, delivering a substantial broadside gain of 14 dBic at 28 GHz, along with an axial ratio (AR) bandwidth of 13% and an impedance bandwidth of 27.3%. These features position it as a highly promising candidate for a wide range of applications. CST Microwave Studio was used for the entire simulation design process.